2016
DOI: 10.1093/cvr/cvw081
|View full text |Cite
|
Sign up to set email alerts
|

Prolyl hydroxylation regulates protein degradation, synthesis, and splicing in human induced pluripotent stem cell-derived cardiomyocytes

Abstract: This study provides the first extensive characterization of the cardiac prolyl hydroxylome and demonstrates that inhibition of α-ketoglutarate hydroxylases alters protein stability, translation, and splicing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 50 publications
3
24
0
Order By: Relevance
“…One of the alternatively spliced genes was cytosolic purine 5′-nucleotidase (NT5C2), which is shown in the Sashimi plot analysis and was verified with quantitative PCR analysis ( Figure 5, A and B). Interestingly, we previously found that DMOG increased exon skipping of NT5C2, which is involved in the NAD salvage pathway (17). Here, we found that the effects of DMOG on exon skipping were abolished for NT5C2 in OGFOD1-KO, which would be consistent with a role for OGFOD1 in mediating these effects on exon skipping.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…One of the alternatively spliced genes was cytosolic purine 5′-nucleotidase (NT5C2), which is shown in the Sashimi plot analysis and was verified with quantitative PCR analysis ( Figure 5, A and B). Interestingly, we previously found that DMOG increased exon skipping of NT5C2, which is involved in the NAD salvage pathway (17). Here, we found that the effects of DMOG on exon skipping were abolished for NT5C2 in OGFOD1-KO, which would be consistent with a role for OGFOD1 in mediating these effects on exon skipping.…”
Section: Resultssupporting
confidence: 87%
“…Because OGFOD1 is known to influence translation (10), we hypothesized that there might be differences in protein synthesis in OGFOD1-KO versus WT cardiomyocytes. To address this hypothesis, we used a previously developed labeling method in iPSC-CMs (17). We cultured OGFOD1-KO and WT cardiomyocytes in media containing light amino acids and then switched them to media containing heavy amino acids and followed the incorporation of the heavy label as a measure of protein synthesis and the loss of the light label as a measure of protein degradation.…”
Section: Resultsmentioning
confidence: 99%
“…Messenger RNA processing and RNA splicing processes are some of the most enriched cellular pathways with proline hydroxylation substrates in Hela cells, which agrees with previous studies that have linked alternative RNA splicing and microRNA processing with hypoxia and oxygen sensing [20, 21, 66, 67]. Our data suggests a potentially critical role of proline hydroxylation pathways on the RNA processing in cancer cells.…”
Section: Discussionsupporting
confidence: 92%
“…Transcription of MYC is upregulated in our infarcted hearts, so it is possible that multiple activation pathways are contributing to the upregulation of Pkm2 expression. Interestingly, mass spectroscopy analysis of prolyl hydroxylation sites regulated by PHD2 in human induced-pluripotent cardiomyocytes found both Pkm2 and hnRNPA1 to be modified (44), suggesting the expression of Pkm2 may also be modulated by posttranslational modifications in response to oxygen levels.…”
Section: Discussionmentioning
confidence: 99%